2005
DOI: 10.1074/jbc.m507559200
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Recognition by 14-3-3 Proteins for Surface Expression of Membrane Receptors

Abstract: Diverse functions of 14-3-3 proteins are directly coupled to their ability to interact with targeted peptide substrates. RSX(pS/pT)XP and RX⌽X(pS/pT)XP are two canonical consensus binding motifs for 14-3-3 proteins representing the two common binding modes, modes I and II, between 14-3-3 and internal peptides. Using a genetic selection, we have screened a random peptide library and identified a group of C-terminal motifs, termed SWTY, capable of overriding an endoplasmic reticulum localization signal and redir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 31 publications
4
72
0
3
Order By: Relevance
“…The construct consisted of a truncated Kir2.1 channel, an RXR motif (from Kir6.2) inserted at the COOH terminus of Kir2.1, and an artificial COOH terminus generated by using a peptide library. With the use of this approach, mode III 14-3-3 binding motifs (located at the extreme COOH terminus) were shown to override an RXR motif located upstream (FIGURE 1B) (12,80). In agreement with other work (55,56,68), the serine or threonine residue at the penultimate position was found to be absolutely required for efficient surface expression (80).…”
Section: -3-3 Proteins and 14-3-3 Binding Motifssupporting
confidence: 75%
See 1 more Smart Citation
“…The construct consisted of a truncated Kir2.1 channel, an RXR motif (from Kir6.2) inserted at the COOH terminus of Kir2.1, and an artificial COOH terminus generated by using a peptide library. With the use of this approach, mode III 14-3-3 binding motifs (located at the extreme COOH terminus) were shown to override an RXR motif located upstream (FIGURE 1B) (12,80). In agreement with other work (55,56,68), the serine or threonine residue at the penultimate position was found to be absolutely required for efficient surface expression (80).…”
Section: -3-3 Proteins and 14-3-3 Binding Motifssupporting
confidence: 75%
“…It should be noted that the proline (P) located at position ϩ2 of the phosphorylation site occurs in only about one-half of known 14-3-3 binding motifs (35). In addition to these two canonical binding motifs, 14-3-3 can bind to the extreme COOH terminus of several proteins, recently defined as a mode III binding site (12,80). The motif is R-X-XpS/pT-X-COOH, with serine or threonine at position Ϫ2 being absolutely required, whereas an arginine (R) residue at position Ϫ5 increases binding affinity (68,80).…”
Section: -3-3 Proteins and 14-3-3 Binding Motifsmentioning
confidence: 99%
“…4C). This was consistent with our earlier finding that the minimal component of C-terminal mode III 14-3-3 binding motif is RXX(S/T)X-COOH (22 seem to be the most critical components of 14-3-3 binding activity within the C-terminal 9 amino acids of GPR15. However, the higher surface expression of S356A compared with that of S359A in spite that both mutants completely lack 14-3-3 binding suggests that Arg 356 may be also a component of the ER localization signal.…”
supporting
confidence: 81%
“…Initial studies to determine 14-3-3 binding sites revealed that their optimal target sequences could be characterized as either mode-1 (RSXpSXP; where pS represents phosphoserine) or mode-2 (RXXXpSXP) (19,37). Using a genetic screen, Coblitz et al (38) identified the C-terminal sequence SWpTX as a "mode-3" 14-3-3 binding motif (38). This collection of target sites is described as canonical, but variations on these motifs have also been documented to mediate 14-3-3 protein interactions with substrates (39).…”
Section: Discussionmentioning
confidence: 99%